2010
DOI: 10.1111/j.1759-1961.2010.00014.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmunity as a principal pathogenic factor in the refined model of neuropsychiatric lupus

Abstract: Objectives:  Over the past decades, the MRL mouse model had shown significant validity in elucidating the pathogenesis of neuropsychiatric lupus erythematosus (NP SLE). However, the possibility that the inherited Fas receptor deficiency (and not autoimmunity) accounts for central nervous system (CNS) damage in the original stock 485 of MRL/MpJ‐Faslpr mice could not be rejected. The aim of the present study was to examine the consequences of autoimmune disease on behavior and brain morphology, while controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…A point of interest is the potential role of the hypothalamus–pituitary–adrenal (HPA) axis in development of the MRL/lpr NPSLE phenotype. Previous studies have shown increased HPA axis activity in this strain, evidenced by increased serum corticosterone levels as well as adrenal hyperplasia [ 57 , 58 ]. Furthermore, treatment with immunosuppression normalized expression of neuroendocrine mediators in MRL/lpr mice, suggesting that neuroendocrine dysregulation is consequent to autoimmunity [ 59 ].…”
Section: Discussionmentioning
confidence: 81%
“…A point of interest is the potential role of the hypothalamus–pituitary–adrenal (HPA) axis in development of the MRL/lpr NPSLE phenotype. Previous studies have shown increased HPA axis activity in this strain, evidenced by increased serum corticosterone levels as well as adrenal hyperplasia [ 57 , 58 ]. Furthermore, treatment with immunosuppression normalized expression of neuroendocrine mediators in MRL/lpr mice, suggesting that neuroendocrine dysregulation is consequent to autoimmunity [ 59 ].…”
Section: Discussionmentioning
confidence: 81%
“…The line was eventually reconstituted and again manifests rapid development of the typical severe autoimmune profile ( http://jaxmice.jax.org/ : re-coding of stock #485-attenuated disease to stock #6825-reconstituted severe line). This serendipitous circumstance permits the differentiation between negative behavioral outcomes that may result from gross peripheral pathology and specific CNS-mediated behaviors [ 14 , 143 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given that there is no evidence of kidney pathology in the disease-attenuated mice, these data confirm the robustness of emotional dysfunction and provide further support that such outcomes are likely a primary manifestation of autoimmunity rather than arising from nonspecific illness and peripheral organ pathology. Finally, the presence of two MRL/lpr strains that share a mutated Fas yet which differ in their autoantibody profile and neurobehavioral manifestations [ 14 , 143 ] is strong evidence that the CNS manifestations in these mice are primarily immunologically mediated, rather than resulting from possible effects of abnormal Fas-mediated apoptosis on brain development or glial function.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this hypothesis, inbreeding has been shown to have significant detrimental effects on the survivorship of mice reintroduced into a natural habitat [38] , offspring survival and reproductive success [39] . Indeed, the effects of laboratory inbreeding can be exemplified by the gradual decline in the autoimmune phenotype ( http://jaxmice.jax.org/strain/006825.html ) and severity of behavioral deficits in the MRL/ lpr substrain [40] , [41] .…”
Section: Discussionmentioning
confidence: 99%